2009
DOI: 10.1002/pd.2418
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cystoscopy for severe lower urinary tract obstruction—initial experience of a single center

Abstract: Percutaneous fetal cystoscopy is feasible using a thinner special cannula for prenatal diagnosis and therapy of LUTO. Prenatal laser ablation of the PUV under cystoscopy may prevent renal function deterioration improving postnatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 29 publications
3
53
0
1
Order By: Relevance
“…Cystoscopy showed significantly better results in terms of the survival rate (62 vs. 11%) and postnatal normal renal function (62 vs. 11%) [22]. The findings we reported are similar to those of Ruano et al [22]. A recent systematic review has concluded that available evidence is still small and consequently fetal cystoscopy for LUTO should still be offered as an experimental intervention.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Cystoscopy showed significantly better results in terms of the survival rate (62 vs. 11%) and postnatal normal renal function (62 vs. 11%) [22]. The findings we reported are similar to those of Ruano et al [22]. A recent systematic review has concluded that available evidence is still small and consequently fetal cystoscopy for LUTO should still be offered as an experimental intervention.…”
Section: Discussionsupporting
confidence: 80%
“…Later, Welch et al reported successful treatment in 6 of 10 fetuses with a purely cystoscopic approach with hydro-ablation or guidewire passage through the urethra [20]. More recently, Ruano et al [22] reported 11 cases with the same approach as in this study, where results were compared with 12 cases managed expectantly. Cystoscopy showed significantly better results in terms of the survival rate (62 vs. 11%) and postnatal normal renal function (62 vs. 11%) [22].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations